Long term effects of intensity of upper and lower limb training after stroke: a randomised trial. Issue 4 (1st April 2002) - Kwakkel, G; Kollen, B J; Wagenaar, R C
Abstract : Objective: To assess long term effects at 1 year after stroke in patients who participated in an upper and lower limb intensity training programme in the acute and subacute rehabilitation phases. Design: A three group randomised controlled trial with repeated measures was used. Method: One hundred and one patients with a primary middle cerebral artery stroke were randomly allocated to one of three groups for a 20 week rehabilitation programme with an emphasis on (1) upper limb function, (2) lower limb function or (3) immobilisation with an inflatable pressure splint (control group). Follow up assessments within and between groups were compared at 6, 9, and 12 months after stroke. Results: No statistically significant effects were found for treatment assignment from 6 months onwards. At a group level, the significant differences in efficacy demonstrated at 20 weeks after stroke in favour of the lower limb remained. However, no significant differences in functional recovery between groups were found for Barthel index (BI), functional ambulation categories (FAC), action research arm test (ARAT), comfortable and maximal walking speed, Nottingham health profile part 1(NHP-part 1), sickness impact profile-68 (SIP-68), and Frenchay activities index (FAI) from 6 months onwards. At an individual subject level a substantial number of patients showed improvement or deterioration in upper limb function (n=8 and 5, respectively) and lower limb function (n=19 and 9, respectively). Activities of daily living (ADL) scores showed that five patients deteriorated and four improved beyond the error threshold from 6 months onwards. In particular, patients with some but incomplete functional recovery at 6 months are likely to continue to improve or regress from 6 months onwards. Conclusions: On average patients maintained their functional gains for up to 1 year after stroke after receiving a 20 week upper or lower limb function training programme. However, a significant number of patients with incomplete recovery showed improvements or deterioration in dexterity, walking ability, and ADL beyond the error threshold.